Arsitektur Perspektif Balanced Scorecard Lembaga Taman Kanak-Kanak Islam Di Indonesia - Lirizki, Riza (STID Al Hadid Surabaya, 2024)
The Balanced Scorecard (BSC) is a contemporary management system widely utilized by both profit and nonprofit organizations to help manage them comprehensively and coherently. Islamic kindergarten institutions are no exception, as they require the BSC tool to be managed more professionally using various relevant perspectives. This study aims to propose an architecture or model of BSC perspectives relevant to the context of Islamic kindergarten institutions, considering that the original BSC perspective architecture is only relevant to business organizational contexts. The research method employed is a qualitative approach using a conceptual paper model. This study finds that for the context of Islamic kindergarten institutions, the relevant BSC perspective model consists of seven perspectives, including financial perspective, customer perspective, curriculum perspective, learning and assessment perspective, administrative perspective, resource perspective, and organizational perspective. The financial perspective is positioned at the top hierarchy, supported by the customer perspective as the financial source. The customer perspective needs to be supported by three perspectives still within the category of goal achievement pathways, namely the curriculum perspective, learning and assessment perspective, and administrative perspective. All perspectives representing goal achievement pathways need to be supported by perspectives reflecting organizational capabilities, namely resource perspective and organizational perspective.